2014
DOI: 10.1002/cncr.28711
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome according to the level of preexisting epidermal growth factor receptor T790M mutation in patients with lung cancer harboring sensitive epidermal growth factor receptor mutations

Abstract: BACKGROUND: Epidermal growth factor receptor (EGFR) T790M mutation drives acquired drug resistance to EGFR tyrosine kinase inhibitors (EGFR-TKIs) in patients with EGFR-mutant lung cancer. However, it was reported that this mutation may exist before drug exposure. The objective of the current study was to evaluate whether the clinical outcomes are affected by the percentage of preexisting T790M mutations within a tumor. METHODS: Pretreatment tissues were collected from 124 patients with advanced non-small cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 25 publications
7
48
2
1
Order By: Relevance
“…In patients with lung cancer, it has been well documented that T790M mutations, although the minority at the time of diagnosis, become predominant after resistance to EGFR inhibitors. 22 In breast cancer, a similar phenomenon is being observed with ESR1. ESR1 is the gene that encodes for ER.…”
Section: Key Pointssupporting
confidence: 56%
“…In patients with lung cancer, it has been well documented that T790M mutations, although the minority at the time of diagnosis, become predominant after resistance to EGFR inhibitors. 22 In breast cancer, a similar phenomenon is being observed with ESR1. ESR1 is the gene that encodes for ER.…”
Section: Key Pointssupporting
confidence: 56%
“…Oxnard et al (25) and Hata et al (28) reported that patients who acquired TKI resistance and harboured the T790M mutation experienced a significantly longer post-progression survival time than patients without the T790M mutation (19 vs. 12 months; P=0.036). However, Lee et al (29) reported that the patients with T790M-positive tumours experienced a shorter overall survival time than those with T790M-negative tumours (median, 9.1 vs. 18.7 months; P=0.018). Numerous factors affect the OS, including the patient's performance status score, cancer therapy, disease stage, and importantly, organ metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…Several investigators applied highly sensitive assays to evaluate whether the presence of T790M subclones in treatment-naïve tumors is associated with shorter duration of response to first-generation TKIs [26,30,31,32,34]. The majority of studies showed a tendency to shorter PFS in patients with this mutation [30,31,32,34,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies showed a tendency to shorter PFS in patients with this mutation [30,31,32,34,44,45]. In support of a biological role of mosaic T790M mutations, Costa et al [32] and Rosell et al [46] observed that low-abundance T790M alleles are characteristic only for lung cancer with EGFR TKI-sensitizing mutations but are uncommon for EGFR wt and KRAS-mutated tumors (see online supplemental materials for these articles).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation